2010
DOI: 10.1166/jnn.2010.2434
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Polyurethane-Grafted Single-Walled Carbon Nanotubes via Click Chemistry

Abstract: Polyurethane (PU)-grafted carbon nanotubes were synthesized by the coupling of alkyne moiety decorated single walled carbon nanotube (SWCNT) with azide moiety containing PU using Cu(I) catalyzed Huisgen [3 + 2] cycloaddition click chemistry. The azide moiety containing poly(s-caprolactone)diol was synthesized by ring-opening polymerization and further used for PU synthesis. Alkyne-functionalizion of SWCNT was completed by the reaction of p-aminophenyl propargyl ether with SWCNT using a solvent free diazotizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The monomer was synthesized using the similar procedure as reported earlier. 11,12,25 3-Chloroperoxybenzoic acid (18.01 g, 75%) with 100 mL DCM was directly mixed with 9.14 g a-chlorocyclohexanone. Stirring was continued for additional 96 h at room temperature.…”
Section: Synthesis Routementioning
confidence: 99%
“…The monomer was synthesized using the similar procedure as reported earlier. 11,12,25 3-Chloroperoxybenzoic acid (18.01 g, 75%) with 100 mL DCM was directly mixed with 9.14 g a-chlorocyclohexanone. Stirring was continued for additional 96 h at room temperature.…”
Section: Synthesis Routementioning
confidence: 99%
“…[2][3] Carbon nanofibers (CNFs) and carbon nanotubes (CNTs) have been extensively studied and applied as fillers for improving various properties of polymers due to their excellent mechanical, electrical and thermal properties. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] CNFs are currently being produced in volume and are significantly less expensive fillers when compared to CNTs. [23][24] Hammel et al found that CNFs are more * Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Cu I -catalyzed alkyne-azide click chemistry can proceed with other chemical reactions, such as ATRP polymerization, with a one-pot procedure; this route could play a major role in the preparation of multifunctional tailored materials based on CNTs. [55] The grafting of PU was controlled by changing the ratio of azide-poly(e-caprolactone)diol as soft segments in PU. [51] MWNTs were functionalized with amphiphilic/Janus polymer brushes using a clickable macro initiator, poly[3-azido-2-(2-bromo-2-methylpropanoyloxy)propyl methacrylate] (polyBrAzPMA), with alkyl bromo functionality, which works as an initiator for ATRP and provides azide functionality for the click coupling reaction.…”
Section: Post-cycloadditionmentioning
confidence: 99%
“…The micelle size and transition temperature can be controlled through the NIPAAm block length. Shape‐memory polyurethane (PU) block‐copolymer‐grafted‐SWNTs were prepared by coupling of an azide‐moiety‐containing PU with alkyne‐moiety‐decorated SWNTs 55. The grafting of PU was controlled by changing the ratio of azide‐poly(ε‐caprolactone)diol as soft segments in PU.…”
Section: Post‐cycloadditionmentioning
confidence: 99%